The Role of Senior Resident Clinics in Plastic Surgery Education in Canada. Issue 3 (August 2021) - McGuire, Connor; Crawley, Emma; Tang, David
Background: Senior resident clinics are a means to encourage independent practice and problem solving and enhance surgical skills. The objective of this study is to investigate senior resident clinics across Canada and their utility in providing comprehensive plastic surgery training. Methods: A web-based survey was sent to all plastic surgery program directors (PDs) and senior residents (SRs; postgraduate years 3, 4, and 5) across Canada. The surveys focused on demographics, clinic structure, procedures commonly performed, perceived autonomy, educational benefit, competency-based design considerations, and areas for improvement. Chi-square tests were used to compare responses between PDs and SRs. Results: A total of 10 PDs (100% response rate) and 26 SRs (41% response rate) responded. Half of the training programs across Canada currently have senior clinics, and the format varies between institutions. Clinics generally focus on hand trauma and aesthetics. Both PDs and SRs felt that there is considerable autonomy for resident care in both the pre/post-operative and operative setting. Common barriers to implementing a senior clinic include not enough staff, not enough time, and the medicolegal risk. Most core competencies are felt to be addressed through the use of senior clinics. Methods to improve senior clinics could include more regular and higher volume clinics, enhanced equipment, and separation of hand and aesthetics clinics. Conclusions: Senior clinics are a useful method to improve plastic surgery education and address many core aspects of plastic surgery training. Implementation of supported clinics focused on hand and aesthetics surgery separately may be useful for training programs that currently lack a senior clinic.